The Influence of Macroeconomic Variables on External Debt in G7 Countries - Ayung Bintari Sakti; Deky Aji Suseno (Journal of Research in Social Science and Humanities, 2025)
The purpose of this research is to use panel data regression analysis and path analysis with the Sobel test mode to examine the impact of macroeconomic factors on foreign debt in G7 nations for the 2019–2023 timeframe.  The findings of the research indicate that while interest rates and the money supply have a negative impact on saves, taxes and GDP have a favorable impact.  Foreign debt is negatively impacted by the variables of taxes, money supply, interest rates, and savings.  Meanwhile, foreign debt is positively impacted by GDP.  In addition, interest rates and money supply have a positive impact on foreign debt through savings, whereas GDP and taxes have a negative impact.